Ética de la naturaleza en pueblos originarios de Colombia (2021)
This work aims to show the ancestral thinking, specifically what has been called by the West an “Environmental” or “Natural” ethic, from the integrity and concern of natural forces and gods to the biocentric conception of life and reality and the cyclical representations of time and space. In ancestral communities such as the Pastos, Arhuacos, and Nükák Makú we can find ontological conceptions which are related to the cultural modalities and ways of life underlining ethics for all living beings of the planet. This legacy, which is still a living heritage in many places of our America, has social and cultural functions that should not only be treated as antique objects, but also as systems of (moral) values that open an intercultural dialogue and illustrate different lifestyles, ways of being, and alternative paths through decolonization processes. These kinds of ethics belong to a matrix that accepts diversity and differences as basic constituents of reality. Life, in its amplitude (not just human life), as a central articulator of the social, cultural, and political dimensions of the community of origin is one of the primary proposals of Ethics of Nature. Despite the differences among the native communities considered in this article, the results of the research have found shared significant themes that constitute the key elements of that ethic: life, death, space, time, responsibility, nature, and ancestrality.